Characterizing Nature and Participant Experience in Studies of Nature Exposure for Positive Mental Health: An Integrative Review - Barnes, Michael R.; Donahue, Marie L.; Keeler, Bonnie L.; Shorb, Cameron M.; Mohtadi, Tara Z.; Shelby, Lacy J. (Frontiers in Psychology, 2019)
A growing number of studies demonstrate significant associations between nature experiences and positive mental health outcomes (e.g., improved mood, decreased stress). However, implementation of this research by practitioners in fields such as urban design or public health has been limited. One reason for this is that it remains unclear what elements of nature and types of participant experience are consistently associated with mental health benefits. As a result, decision-makers who aim to enhance mental health in cities have little guidance about which elements of nature and types of experiences in natural areas may lead to positive mental health outcomes. We reviewed 30 studies with 41 distinct exposures in nature that elicited positive mental health benefits and characterized the elements of nature found at these sites, as well as aspects of participants’ experience. Elements of natural areas considered include: forest, managed grass, and water as dominant land cover types, specific water features (e.g. small ponds, fountains) and built features (e.g. trails, paths). The majority of the studies we reviewed assessed the experiences of individuals (vs. in groups) participating in walks during warmer seasons. Most studies did not describe the “nature of the nature” associated with positive mental health outcomes. We contacted authors and used Google Earth imagery to reconstruct the specific natural elements, landscape typology, and site adjacencies present in past studies. We recommend specific ways researchers could better and more transparently document important elements of nature and participant experience in study design and reporting that will enhance the planning and design relevance of their work.